In Defense of Young Adult Literature - Driscoll, Marc (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
English language arts teachers have forever relied on the English literature canon for their selection of text to use in the classroom. This article asks the question if this method is the most effective way to choose classroom texts based on the interest level of the students. It is argued that young adult literature, or literature that is written about characters that are the same age as students facing similar issues, can capture the interest of students and motivate them to be engaged in the English language arts lessons.